Complete mitochondrial genome sequence of lettuce pathogenic fungus, Fusarium oxysporum f. sp. lactucae 16-086 - Woochan Kwon; Jongsun Park; Jung-Bun Kim; Mi-Jeong Park; Tae-Sung Kim (Mitochondrial DNA. Part B. Resources, 2019)
Fusarium oxysporum f. sp. lactucae 016-086 is a plant pathogenic filamentous fungus isolated from wilted lettuce in Korea. We reported complete mitochondrial genome sequence of F. oxysporum f. sp. lactucae 016-086. Total length of this mitogenome is 41,826 bp and it encoded 42 genes (14 protein-coding genes, 2 rRNAs, and 26 tRNAs). Nucleotide sequence of coding region takes over 30.6%, and overall GC content is 32.5%. Phylogenetic tree of Fusarium mitochondrial genomes presented distinct clades along with nine formae speciales. This mitogenome will contribute distinguishing formae speciales of F. oxysoporum claearly with additional mitogenomes sequenced in the near future.